HUKUM NATING DALAM SYARIAT ISLAM - Distiliana, Distiliana (Solusi, 2018)
Dempo Utara Pagaralam is the result of field research to know the law of practice nating in syariat islam in mountain village of agung kec. Dempo Utara Pagaralam. Data that needs to be collected in this study with methods of observation, interviews and documentation. After the data is collected, the data is processed and analyzed by qualitative descriptive method which is the conclusion of data starting from the aspect of syariat Islam then drawn to the facts of field which is special that is about the utilization of guarantee goods by the receiver of pawn (murtahin). Result of research from 3 case practice of nating in village of mount agung kec. Dempo Utara Pagaralm concluded the nating contract (pledge) is valid because it fulfills the requirements and rukun pawn based on Islamic Shari'ah which is dilafazkan, aqil, baligh, proficient, intelligent and accompanied by witness and proof of kesepitaatan in writing. The amount of money that is used as a debt of about 5-20 million rupiah in addition, with a guarantee of agricultural land with an area of ​​approximately 400m2 - 6540m2. The treatment of coffee plantations as collateral goods is taken over completely from start of management until the coffee garden and murtahin products do not provide loans to the rahada (pawns) money if the rahin does not submit certificates and collateral goods as collateral. From land use (collateral goods) murtahin get profits ranging from 50-90% of the amount of debt. According to the analysis of the practice of nating in the village of majestic mountain kec. North Dempo is not in accordance with Islamic Shari'a. It is recommended for the people of the village of mount Agung. Dempo north to implement the practice of nating according to Islamic Shari'a